Historical Interpretation: Traces of Classic Culture in Situbondo, East Java - Sumarjono Sumarjono; Kayan Swastika; Mohamad Na'im; Akhmad Ryan Pratama; Robit Nurul Jamil (Budapest International Research and Critics University, 2022)
Relics of Hindu-Buddhist influence that indicate influence in the political field are inscriptions found, such as the Yupa inscription, Pasir Kolengkak, Tugu, Kota Kapur, Kedukan Bukit, Tuk Mas, Dinaya, Canggal, and others. These inscriptions show the Hindu-Buddhist patterned kingdoms. Classical historiography of Indonesia still does not mention many archaeological remains from Kab. Situbondo concretely, is like a puzzle, still topsy-turvy, aka not yet organized. The information that is available is fragmentary and there is still little further research that triggers multiple interpretations of the existence of these classic archaeological remains. Speaking of archaeological remains which are assumed to come from classical timelines, the indicators of findings require comprehensive research. Archaeological remains, especially those from Situbondo Regency, are deemed necessary to be presented scientifically. This research is designed as historical research. The implementation of the research was carried out using the historical method by utilizing the archaeological methodological approach. The position of the methodological approach of prehistoric archeology here is as a support for the historical method. Based on the results of this research, Situbondo found some information that 1. Situbondo is a rich district based on historical heritage, the ancient (classical) monarchy period spread over the three regions. 2. Real Number of Cultural Conservation Objects 26 Findings. 3. The historical construction of various classical heritages has limited resources considering that there are still many remains with the status of objects suspected of being ODCB cultural reserves. 4. The results of the archaeological data in this study which are the main reference for disclosing the history of classical culture in Situbondo, the archaeological data are divided into five parts; artifacts, ecofacts, features, archaeological sites and areas. These five types of data become the study of researchers to interpret classical culture in Situbondo. From the various findings of the scientific description, it is then interpreted from a social, economic and political point of view.